MEMBANGUN ORGANISASI KEPEMUDAAN - Dedy Kustiyono (Batara Wisnu : Indonesian Journal of Community Services, 2021)
In the development of the movement, it is not uncommon for us to find many youth organizations collapsing and overlapping interests only due to differences in perceptions and mistakes in managing their organizational operations, as if youth organizations are considered "mediocre" organizations, an organization that does not need to be managed too seriously. So that we can see the results, only giving birth to youth organizations that are uncompetitiveness, organizations that do not have benchmarks, and are only satisfied if they are able to survive for a period of time or live only on certain events, and sometimes even become organizations that are unable to bring up a cadre of successors. which resulted in the organization suspended animation. The results of a survey of several youth organizations in Tangerang City, at least can describe the existing conditions of youth organizations in Tangerang City, which then will also be faced with the fact that currently Indonesia already has Law Number 40 of 2009 concerning Youth. This regulation immediately demands that every youth organization must be a healthy organization with a clear and measurable vision and mission supported by orderly organizational management as well